Analisis Dinamika Sikap Forgiveness pada Santi Menghafal Al Qur’an di Pondok Pesantren Maunah Sari Kota Kediri - Moh. Hapid Muzaki; Uswatun Hasanah (Indonesian Journal of Humanities and Social Sciences, 2021)
This article discusses the way students who memorize the Qur'an in building forgiveness in order to address the problems of social life experienced and reconcile the social relationships faced in an effort to build the harmony of life. How do students who memorize the Qur'an address the problem of social conflict? Forgive or take revenge. If the answer to the question becomes material to be identified in order to know the dynamics of forgiveness of the students who memorize the Qur'an. The research that the researchers conducted is included in qualitative research, the approach used is phenomenology. The results of the analysis forgiveness attitude in students who memorize are total forgiveness in the sense of acceptance of transgressor errors sincerely without revenge.